Biodiversity - Center for Natural Resources (EDIS)
Biodiversity or biological diversity is a relatively new term in ecology. It became popular in the 1980s and is not yet properly understood by all non-ecologists. Biodiversity refers to the variety and richness among living organisms and the ecological systems and processes of which they are a part. There are three levels of biodiversity: habitat or ecosystem diversity, genetic diversity, and species diversity. This publication was produced by the Center for Natural Resources at the University of Florida. CNR 4 is part of a Program Summary Series. First published: September 2000. Minor revision: March 2003.